The Periodic Carbon Stock Calculation and Monitoring of Flora and Fauna of the Watershed Rehabilitation Area of PT Asmin Bara Bronang: The Periodic Carbon Stock Calculation and Monitoring of Flora and Fauna of the Watershed Rehabilitation Area of PT Asmin Bara Bronang - Soebagiyo, Siti Maimunah; Sushardi; Galang Indra Jaya; Suwito Setyo Budi; Hasan Mudzakir; JH Samek (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2025)
Watershed rehabilitation is an important effort in restoring natural conditions, especially along river flows for conservation efforts. Observations are still being made on permanent plots observed from 2020 for 250ha with 51 permanent plots were made spread evenly with a plot size of 20x20meters. The sampling intensity taken for this periodic observation was 0.816% using a carbon and biodiversity calculator from Michigan State University 2018. The results of the 2024 monitoring show that there is an increase in the amount of carbon by 21,069tons of carbon in all permanent plots in the area and an increase in the total carbon dioxide equivalent in the area of 77.26tons of carbon increased from 2020 and on each hectare of the area there is an increase in the amount of carbon over a period of one year. The increase trees species in the area is known to have 15 species, with the Menhinnick index 0.5; Margalef's index 2.; Shannon diversity indices 1.48; Simpson diversity indices 0.71; The frequency appears of species 0.55. The types of wildlife found of direct encounters, nests, footprints, feces, voices and feathers, were directly found orangutan, deers, birds, bears, and wildboars.